Characterization of Chicken Tumor Necrosis Factor-α, a Long Missed Cytokine in Birds - Rohde, Franziska; Schusser, Benjamin; Hron, Tomáš; Farkašová, Helena; Plachý, Jiří; Härtle, Sonja; Hejnar, Jiří; Elleder, Daniel; Kaspers, Bernd (Frontiers in Immunology, 2018)
Tumor necrosis factor-α (TNF-α) is a pleiotropic cytokine playing critical roles in host defense and acute and chronic inflammation. It has been described in fish, amphibians and mammals but was considered to be absent in the avian genomes. Here we report on the identification and functional characterization of the avian orthologue. The chicken TNF-α (chTNF-α) is encoded by a highly GC-rich gene, whose product shares with its mammalian counterpart 45% homology in the extracellular part displaying the characteristic TNF homology domain. Orthologues of chTNF-α were identified in the genomes of 12 additional avian species including Palaeognathae and Neognathae, and the synteny of the closely adjacent loci with mammalian TNF-α orthologues was demonstrated in the crow (Corvus cornix) genome. In addition to chTNF-α, we obtained full sequences for homologues of TNF-α receptors 1 and 2 (TNFR1, TNFR2). ChTNF-α mRNA is strongly induced by Lipopolysaccharide (LPS) stimulation of monocyte derived, splenic and bone marrow macrophages and significantly upregulated in splenic tissue in response to i.v. LPS treatment. Activation of T-lymphocytes by TCR crosslinking induces chTNF-α expression in CD4+ but not in CD8+ cells. To gain insights into its biological activity, we generated recombinant chTNF-α in eukaryotic and prokaryotic expression systems. Both, the full-length cytokine and the extracellular domain rapidly induced an NFκB-luciferase reporter in stably transfected CEC-32 reporter cells. Collectively, these data provide strong evidence for the existence of a fully functional TNF-α/TNF-α receptor system in birds thus filling a gap in our understanding of the evolution of cytokine systems.